Briefly noted. - Fallows, David (Early Music, 2000)
Deals with books that may be of interest to early music researchers. Book titled 'Obiter Scripta,' edited by Jacqueline Gray; Book titled 'Der Fondo Cappella Sistina der Biblioteca Apostolica Vaticana,' by Bernhard Janz; Book titled 'Thesaurus musicarum latinarum: Canon of data files,' edited by Thomas J. Mathiesen.